Optimization of Cropping Intensity in Batujai Irrigation Areas Using SRI Method and CROPWAT 8.0 - Dewandha Mas Agastya; Muh Bagus Budianto; I Ketut Budastra; I Wayan Yasa (agriTECH, 2026)
The Batujai Reservoir has been in operation since 1982 and remains functional in 2025. However, long-term sediment accumulation has gradually reduced its effective storage capacity. Several studies have shown that under limited water availability, improving irrigation efficiency is crucial. The System of Rice Intensification (SRI) method can be adopted as a water-saving cultivation practice to enhance water productivity and sustain rice yield. Therefore, this study aims to determine the capability of the SRI planting method in achieving cropping intensity in areas with limited water resources, drought, and climate change pressure. An assessment of reservoir water availability was conducted using long-term discharge data from 1997 to 2024. Inflow reliability was then determined by classifying hydrological conditions into wet (Q35%), normal (50%), and dry (65%) years based on frequency analysis applying the Weibull distribution. Evapotranspiration was examined based on climatological data, including temperature, humidity, wind speed, and sunlight duration. The potential evapotranspiration value was calculated using CROPWAT 8.0 software, and the highest value was obtained in August at 4.35 mm/day. The SRI method had an intermittent irrigation concept that did not require land to be submerged in water continuously. The height of the water pool required was 2 cm, and the filling of the cracks was 1.1 cm high. The highest irrigation water requirement was 0.878 l/s/ha in December for the conventional method and 1.480 l/s/ha in April for the SRI method. Based on the results of simulation calculations and reservoir operation optimization, a comparison of the SRI and conventional planting methods yielded cropping intensity values of 275.34% and 274.38% for the November I planting season. The success indicators of simulation modelling and reservoir operation optimization met the minimum k-factor thresholds for irrigation and domestic water needs of 0.75 and 0.85, respectively.